A programmable platform for sub-second multichemical dynamic stimulation and neuronal functional imaging in C. elegans. Issue 3 (9th January 2018) - Rouse, T.; Aubry, G.; Cho, Y.; Zimmer, M.; Lu, H.
Abstract : This microfluidic platform enables monitoring neuronal activity of C. elegans in response to dynamic multichemical cues. Abstract : Caenorhabditis elegans ( C. elegans ) is a prominent model organism in neuroscience, as its small stereotyped nervous system offers unique advantages for studying neuronal circuits at the cellular level. Characterizing temporal dynamics of neuronal circuits is essential to fully understand neuronal processing. Characterization of the temporal dynamics of chemosensory circuits requires a precise and fast method to deliver multiple stimuli and monitor the animal's neuronal activity. Microfluidic platforms have been developed that offer an improved control of chemical delivery compared to manual methods. However, stimulating an animal with multiple chemicals at high speed is still difficult. In this work, we have developed a platform that can deliver any sequence of multiple chemical reagents, at sub-second resolution and without cross-contamination. We designed a network of chemical selectors wherein the chemical selected for stimulation is determined by the set of pressures applied to the chemical reservoirs. Modulation of inlet pressures has been automated to create robust, programmable sequences of subsecond chemical pulses. We showed that stimulation with sequences of different chemicals at the second to sub-second range can generate different neuronal activity patterns in chemosensory neurons; we observed previously unseen neuronal responses to a controlled chemical stimulation. Because of the speed and versatility of stimulus generated, this platform opens new possibilities to investigate neuronal circuits.